Relevance of Cybersecurity Education at Pedagogy Levels in Schools - Eric Amankwa (Research Highlights in Mathematics and Computer Science Vol. 7, 2023)
Today, the internet extensively impacts people’s lives through improved com- munications, interactions, and the exchange of information. Despite all these positive effects, it also causes in significant negative issues. Over the recent years, cases of online fraud, cyber-bullying, racial abuse, gambling, and por- nography have increased due to the lack of self-control and overall awareness among internet users. Therefore, there is a need to create awareness and training on cybersecurity in schools to protect students from cyber-bullying, online fraud, and being targets of prejudice. Research reveals that the level of self-control and awareness among internet users is still moderate and low. To ensure cybersecurity awareness and knowledge among internet users, young people need to get educated on how to operate safely in cyberspace. This education will guarantee that they understand how to protect themselves from cybercrimes. To this extent, this research paper will explore the essence of cybersecurity education in schools and provide strategies that educators can utilize to promote cybersecurity education across learning institutions. This paper will thus conclude how cybersecurity training can be implemented in a learning institution.